Microtonal Analysis of "Blue Notes" and the Blues Scale - Cutting, Court B (Empirical Musicology Review, 2019)
Microtonal evaluation of blue notes in the early blues scale by empirical pitch measurement and statistical characterization has not yet been performed in existing research. To address this, fifteen recorded classic blues performances by acknowledged early masters of the blues were studied. Computer based methods were used to collect the audio frequencies of note samples from each performance. Each note had its frequency ratio with respect to the average tonic tone for the performance converted to microtonal cents format. Cluster analysis was performed on these note collections to identify individual note clusters. The fourth and fifth were clearly identified. Three principal "blue note" clusters were isolated with means of 319.1, 582.8, and 1037.9 cents. These values corresponded closely to the harmonic half diminished seventh chord (i.e. 1, ♭3, ♭5, ♭7 with harmonics 5:6:7:9). The "neutral" third was confirmed to occur in this sample. A similar blending of the perfect fourth and tritone was demonstrated in this study. The flat 7th presented as three separate clusters. Several clusters idiosyncratic to individual performers were also identified. Findings are discussed with regards to the array of theories proposed to explain the blues.